الأدوار المستقبلية لأعضاء هيئة التدريس بالجامعات المصرية في ضوء أهداف التنمية المستدامة: رؤية مصر 2030 م. - رومان، هاني سليمان داود (جامعة القاهرة - كلية الدراسات العليا للتربية, 2022)
هدف هذا البحث إلى تعرف الأهداف الرئيسة لاستراتيجية التنمية المستدامة: رؤية مصر 2030م، وتحديد أدوار أعضاء هيئة التدريس بالجامعات المصرية في ضوء الوظائف الحالية للجامعات، وذلك بغرض وضع تصور للأدوار المستقبلية لأعضاء هيئة التدريس بالجامعات المصرية في ضوء أهداف التنمية المستدامة. وقد استخدم البحث المنهج الوصفي التحليلي، عن طريق تحليل الأدبيات والدراسات السابقة التي اهتمت بدراسة التنمية المستدامة من حيث مفهومها، وخصائصها، وأبعادها، ومبادئها، وأهميتها، وأهدافها، ومتطلباتها، والتحديات التي تواجه تحقيقها، والمحاور الرئيسة لاستراتيجية التنمية المستدامة: رؤية مصر 2030م، والأهداف الاستراتيجية للتعليم العالي والجامعي طبقا لرؤية مصر حتى عام 2030م، وتحليل الأدبيات المتعلقة بوظائف أعضاء هيئة التدريس بالجامعات المصرية والتي تنبثق بدورها من وظائف التعليم الجامعي، وهي: التدريس، والبحث العلمي، وخدمة المجتمع. وفي ضوء أهداف التنمية المستدامة والأدوار الحالية لأعضاء هيئة التدريس تم وضع تصور للأدوار المستقبلية لأعضاء هيئة التدريس بالجامعات المصرية في ضوء أهداف التنمية المستدامة. The Aim of this Research is to identify the main objectives of the Sustainable Development Strategy: Egypt’s vision 2030, and to determine the roles of faculty members in Egyptian universities in light of the current functions of universities, in order to develop a vision for the future roles of faculty members in Egyptian universities in light of the Sustainable Development goals. The research used the Descriptive Analytical approach by analyzing the literature and previous studies, which focused on studying Sustainable Development in terms of its concept, characteristics, dimensions, principles, importance, objectives, requirements, challenges facing their achievement, and the main axes of the Sustainable Development strategy: Egypt’s Vision 2030, and the strategic goals of higher and university education according to Egypt’s vision until 2030, and an analysis of the literature related to the functions of faculty members in Egyptian universities, which in turn emanate from the functions of university education, namely: Teaching, Scientific Research, and Community Service. In light of the Sustainable Development goals and the current roles of faculty members, a vision was developed for the future roles of faculty members in Egyptian universities in light of the Sustainable Development goals.
Keywords: أعضاء هيئة التدريس -- التنمية المستدامة -- التعليم الريادي -- جودة التعليم -- الجامعات المصرية